Exploring Interactive Simulations as a Powerful Tool in STEM-PBL Approach in Physics - Stanescu, Mariana Mirela (European Scientific Journal, ESJ, 2020)
Recent educational studies have shown that interactive simulations inteaching science can improve motivation, understanding and active learning.This article aim wasto investigate potential of interactive simulation in STEMapproach in the case of complex phenomena related to light. PhET is a learningenvironment that integrates virtual labs for various disciplines, widely used ineducation. The descriptive research method achieved its goal and confirmedthat simulations in physics represent a valuable tool for the acquisition andconsolidation of STEM skills.